Late Holocene aridification recorded in the stable carbon and nitrogen isotope composition of soils from Nainital, Lesser Himalaya. (22nd February 2018) - Khan, Imran; Amir, Mohd; Paul, Debajyoti; Srivastava, Pankaj
Abstract: This study incorporates micromorphology, geochemistry, and stable carbon and nitrogen isotope compositions of soil organic matter (δ 13 C and δ 15 N) in a radiocarbon-dated Holocene Alfisol section from Nainital, northwest Himalaya, India to understand pedogenic and vegetation response to changing Indian Summer Monsoon (ISM). Soil micromorphology suggests this soil to be an Alfisol that formed in semiarid to humid conditions. Extensive illuviation with thick clay pedofeatures found in the Bt-horizon suggests wet conditions and intense monsoon during early to middle Holocene (9.0–∼4.6 ka). The δ 13 C varies from −14.2‰ to −22.6‰ and reflects abrupt changes in the proportions of C3 and C4 plants in the ecosystem during late Holocene. An average δ 13 C of −21.6 ± 1.0‰ during early to middle Holocene (9.0–4.6 ka) indicates that the vegetation was dominated by C3 plants growth under hot humid and strong monsoonal conditions. On the other hand, δ 13 C (−16.7 ± 2.1‰) during late Holocene (∼4−1 ka) suggests distinct vegetation shift towards increasing C4 plants abundance related to aridification (weak ISM) at ∼4 ka. The pattern of δ 15 N variability in the soil is similar to that observed for the δ 13 C variability in the profile. The δ 15 N varies from +4.4% to +8.3%, with significantly more positive values during late Holocene (weaker monsoon) compared to early to middle Holocene (stronger monsoon), consistent with the relationship between δ 15 N and mean annual precipitation observed on a global scale. Our study demonstrates a strong and rapid adjustment of vegetation in response to ISM variability during Holocene.